ENCOURAGING ILLOCUTIONARY SPEECH ACTS IN THE SONG LYRICS OF THE GREATEST SHOWMAN MOVIE BY MICHAEL GRACEY - Zaki, Alfry Reynand (Universitas Pakuan, 2025)
The lyrics of a song are not just a collection of beautiful words; they also serve as a form of communication that can carry pragmatic meanings, including speech acts that encourage. This research aims to identify and analyze illocutionary acts with encouraging functions in the lyrics of the movie The Greatest Showman. The encouraging function is understood as a type of utterance that offers support, enthusiasm, and motivation to the interlocutor or listener. This study employs a descriptive qualitative approach, using the speech act theory from Searle (1970) and Searle Vanderveken (1985) as the basis for classification. The classification includes five types of speech acts: assertive, directive, commissive, expressive, and declarative. The data consist of lyrics collected from nine songs in the film, analyzed in the context of speech events, propositional content, and the effects of the utterances. The results indicate that the encouraging function in the song lyrics can manifest through various types of speech acts, not only in the form of explicit invitations but also through personal statements, commitments, and emotional expressions. Thus, the song lyrics in this movie serve not only as entertainment but also as a practical and pragmatic motivational tool.